EFFECT OF COMMUNICATION LITERACY INTERVENTION (CLI) ON SIGN LANGUAGE KNOWLEDGE (SLK) AMONG SPECIAL NEEDS DEAF AND DUMB COLLEGE STUDENTS IN NIGERIA - Ikechukwu, Egbe (Ph.D), Cajetan; Cosmas, Ugwu (Ph.D), Uchenna; Tolu, Obateru (Ph.D), Oluwatoyin (International Journal of Psychosocial Rehabilitation, 2021)
Communication is indispensable in human populations. This study investigated the effect of communication literacy intervention (CLI) on sign language knowledge (SLK) among special needs deaf and dumb college students (SNDDCS) in Nigeria. The study adopted an experimental research design, using purposive sampling of 48 SNDDCS in Nigeria between March and June 2021. The eligible participants were randomly assigned to either the treatment (n=24) or control (n=24) group. Only the participants in the treatment group were exposed to the CLI manual, while both groups participated in pre- and post-test measures using the Sign Language Knowledge Questionnaire (SLKQ), which had a reliability index of r=0.87. IBM SPSS version 22 was used for all statistical computations, with results considered significant at p≥0.05.The findings showed that participants in the treatment group recorded very high SLK scores in the post-test (80.6%) and follow-up (81.7%) measures, compared to their low pre-test SLK score (46.2%), indicating a significant increase in SLK. Statistically significant differences were observed within demographic variables and intervals. No significant differences were found based on gender (p=0.090>0.05) and location (p=0.680>0.05), but differences were observed based on age by birth (p=0.002